Method for preparing perfluoropolyether carboxylic acid from perfluoropolyether oil
By carrying out catalytic cracking reaction under mild conditions under the action of a magnesium-based catalyst, the problems of low selectivity and low yield of perfluoropolyether single-ended carboxylic acid are solved, and the efficient preparation of active perfluoropolyether single-ended carboxylic acid is achieved. , the product has high weight average molecular weight and functionality, and is suitable for the production of a variety of functional materials.
Patent Information
- Application Number
- CN202411666645.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
In the prior art, the single-ended carboxylic acid of perfluoropolyether has low selectivity and low yield, the catalytic cracking reaction conditions are harsh and difficult to control, and the weight average molecular weight of the active perfluoropolyether carboxylic acid is insufficient.
Perfluoropolyether oil and magnesium-based catalyst are mixed under mild conditions, and perfluoropolyether oil is cracked highly selectively through the action of magnesium-based catalyst to obtain single-ended carboxylic acid with high weight average molecular weight. acid.
The active perfluoropolyether single-ended carboxylic acid is prepared with high selectivity and high yield. The weight average molecular weight of the product reaches more than 4,000 and has high functionality. It is suitable for the production of a variety of functional materials.
Smart Images

Figure CN119463153A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the synthesis of perfluoropolyether carboxylic acid, in particular to a method for preparing perfluoropolyether carboxylic acid by using perfluoropolyether oil, belonging to the technical field of synthesis of functional perfluoropolyether carboxylic acid. Background Art
[0002] Perfluoropolyether oil (PFPE) is a perfluoropolymer compound, a synthetic polymer that is liquid at room temperature, and its molecules are composed of only three elements: C, F, and O. Since fluorine atoms have strong electronegativity and the carbon chain is shielded by fluorine atoms, compared with hydrocarbon polyethers, perfluoropolyethers have many excellent properties, such as chemical inertness, thermal oxidation stability, compatibility, flame retardancy, and radiation resistance.
[0003] Perfluoropolyether carboxylic acid containing active groups is a relatively expensive raw material. It can be used as a raw material for perfluoropolyether modified materials and applied to various functional materials. Perfluoropolyether carboxylic acid has the following characteristics: low friction coefficient, high load resistance and good lubricity; excellent chemical stability and weather resistance; low surface energy and good solvent resistance; the type of perfluoropolyether carboxylic acid depends on the monomer used for polymerization. According to the different monomers and polymerization methods, there are currently four main types of perfluoropolyether carboxylic acid products, namely Z, Y, K and D types, of which the first two are photocatalytic polymerization products and the latter two are anionic polymerization products.
[0004] In the prior art, titanium oxide, iron oxide, calcium oxide, zirconium oxide, ferrosoferric oxide, etc. are used as catalysts to catalyze the preparation of perfluoropolyether single-end carboxylic acids. However, there are problems such as low selectivity (<15%), low effective yield of target product (<20%), harsh process conditions for catalytic cracking reaction, cracking as a self-disproportionation exothermic reaction process, difficult to control the reaction, and the weight average molecular weight of the active perfluoropolyether carboxylic acid after separation is less than 3500. Summary of the invention
[0005] In view of the problems of low selectivity and low yield of perfluoropolyether single-end carboxylic acid in the prior art, the present invention provides a method for preparing perfluoropolyether carboxylic acid by using perfluoropolyether oil, wherein the perfluoropolyether oil is catalytically cracked with high selectivity under the action of a magnesium-based catalyst to obtain an active perfluoropolyether single-end carboxylic acid (Z type), with mild synthesis conditions, a short and easy-to-control process, and a high yield. The active perfluoropolyether single-end carboxylic acid product can be modified with functional functional groups to obtain fluorine-modified materials for various fields, and can be used in the fields of coatings and surface treatment materials, etc., with broad market prospects.
[0006] In order to achieve the above technical objectives, the technical solutions adopted by the present invention are as follows: A method for preparing perfluoropolyether carboxylic acid by using perfluoropolyether oil, the method specifically comprising: firstly mixing perfluoropolyether oil and a fluorine-containing solvent in the presence of a magnesium-based catalyst to obtain a reaction mixture, then separating the reaction mixture, and sequentially acidifying and purifying the separated filtrate to obtain the target perfluoropolyether carboxylic acid.
[0007] Preferably, the weight average molecular weight of the perfluoropolyether oil is not less than 10,000, preferably not less than 20,000.
[0008] Preferably, the fluorine-containing solvent includes one or more of m-ditrifluorotoluene, trichlorotrifluoroethane, dichloropentafluoropropane, and hexafluoroisopropanol, preferably trichlorotrifluoroethane.
[0009] Preferably, the volume ratio of the perfluoropolyether oil to the fluorinated solvent is 1:0.5-5, preferably 1:0.8-3.
[0010] Preferably, the magnesium-based catalyst is used in an amount of 0.1-2% by mass of the perfluoropolyether oil, preferably 0.5-1.5%.
[0011] Preferably, the magnesium-based catalyst is prepared by the following method: first dissolving a water-soluble magnesium salt in water to obtain a magnesium-based salt solution, then adding a soluble carbonate to the magnesium-based salt solution for precipitation reaction, and finally heat-treating the solid product obtained by the reaction to obtain the magnesium-based catalyst.
[0012] Preferably, the magnesium-based catalyst is prepared by the following method: firstly dissolving a water-soluble magnesium salt and a water-soluble zinc salt in water to obtain a magnesium-based salt solution, then adding a soluble carbonate to the magnesium-based salt solution for precipitation reaction, and finally heat-treating the solid product obtained by the reaction to obtain the magnesium-based catalyst; Further preferably, the magnesium-based catalyst is prepared by the following method: firstly dissolving a water-soluble magnesium salt, a water-soluble zinc salt, and a water-soluble manganese salt in water to obtain a magnesium-based salt solution, then adding a soluble carbonate to the magnesium-based salt solution for a precipitation reaction, and finally heat-treating the solid product obtained by the reaction to obtain a magnesium-based catalyst.
[0013] Preferably, the water-soluble magnesium salt includes one or more of magnesium nitrate, magnesium sulfate, and magnesium chloride. The water-soluble zinc salt includes one or more of zinc nitrate, zinc sulfate, and zinc chloride. The water-soluble manganese salt includes one or more of manganese nitrate, manganese sulfate, and manganese chloride. It should be noted that each metal salt should include their hydrates.
[0014] Preferably, in the magnesium-based catalyst, the molar ratio of magnesium element, zinc element and manganese element is 1:0~0.35:0~0.12, preferably 1:0.15~0.3:0.05~0.1.
[0015] Preferably, the soluble carbonate includes one or more of sodium carbonate, potassium carbonate, lithium carbonate and ammonium carbonate.
[0016] Preferably, the carbonate is added in an amount such that the content (molar content) of carbonate ions in the reaction system is not less than 1.2 to 1.5 times the content (molar content) of magnesium ions.
[0017] Preferably, the precipitation reaction temperature is 20-60°C, preferably 30-50°C. The precipitation reaction time is 1-12 hours, preferably 2-10 hours. And / or The heat treatment is calcining at a temperature of 400-900° C. for 1-8 hours, preferably calcining at a temperature of 500-800° C. for 2-6 hours.
[0018] Preferably, the mixing reaction is a stirring reaction, the stirring reaction temperature is 120-280° C., preferably 150-250° C. The stirring reaction time is 10-90 min, preferably 15-60 min.
[0019] Preferably, the acidification is specifically as follows: adding a solvent (such as perfluoropolyether solvent SV70) and a hydrochloric acid solution to the filtrate and then stirring. The amount of the solvent added is 0.05 to 0.3 times the volume of the filtrate. The hydrochloric acid solution is a dilute hydrochloric acid solution with a mass concentration of 3 to 15%, and the amount of the hydrochloric acid solution added is 0.2 to 1 times the volume of the filtrate. The speed of the stirring treatment is 300 to 1000 rpm, and the time of the stirring treatment is 1 to 30 minutes.
[0020] Preferably, the purification is specifically as follows: adding a solvent (such as acetonitrile) to the acidified liquid obtained after the acidification treatment for extraction, collecting the lower layer solution after standing, and performing a reduced pressure evaporation treatment to remove the solvent.
[0021] In the present invention, relatively cheap inert perfluoropolyether oil is used as raw material, and catalytic cracking is carried out using a magnesium-based catalyst to obtain a relatively expensive active perfluoropolyether single-end carboxylic acid product under relatively mild reaction conditions, which has extremely high added value.
[0022] In the present invention, the magnesium-based catalyst can not only realize the catalytic cracking of perfluoropolyether oil, but also has a high selectivity of active perfluoropolyether single-end carboxylic acid. In particular, when a certain amount of zinc element (in the form of zinc oxide) is contained in the magnesium-based catalyst, the proportion of active perfluoropolyether single-end carboxylic acid in the reaction mixture obtained by the mixed reaction will be significantly improved. In the provided magnesium-based catalyst, the preferred molar ratio between the magnesium element (in the form of magnesium oxide) and the zinc element is 1:0.15~0.3. Within this range, the selectivity of catalytic cracking of perfluoropolyether oil to obtain active perfluoropolyether single-end carboxylic acid is relatively high. When the content of zinc element is too high or too low, the selectivity of active perfluoropolyether single-end carboxylic acid will be reduced to a certain extent.
[0023] In the present invention, the weight average molecular weight of the perfluoropolyether oil used is generally above 10,000, and then the active perfluoropolyether single-end carboxylic acid product with a weight average molecular weight of more than 4,000 is obtained by catalytic cracking (the end product application test of this type of active perfluoropolyether single-end carboxylic acid product shows better wear resistance, steel wool resistance, eraser resistance>12,000 times, and water drop angle>100°). It should be noted that when a certain amount of manganese element (in the form of manganese oxide) is also contained in the magnesium-based catalyst, the weight average molecular weight of the obtained active perfluoropolyether single-end carboxylic acid can be controlled at about 4,500 to 5,500. In the provided magnesium-based catalyst, the preferred molar ratio between magnesium element and manganese element is 1:0.05 to 0.1. Within this range, the molecular weight of the active perfluoropolyether single-end carboxylic acid obtained by catalytic cracking of perfluoropolyether oil is closer to the target demand. When the content of manganese element is too high or too low, it will cause a large fluctuation in the molecular weight of the active perfluoropolyether single-end carboxylic acid to a certain extent.
[0024] In the present invention, when preparing the magnesium-based catalyst, a soluble magnesium-based salt (including a water-soluble zinc-based salt and / or a water-soluble manganese salt) is first dissolved in water to obtain a mixed salt solution, and then a soluble carbonate is added to the mixed salt solution for precipitation reaction. The catalyst preparation process is to first add a soluble salt and then add a carbonate in order to obtain a metal precipitated salt, so that the oxide can be obtained by subsequent calcination, so the carbonate cannot be replaced by a base such as a hydroxide.
[0025] In the present invention, acidification treatment of the reaction filtrate after catalytic cracking can improve the subsequent separation column effect.
[0026] Compared with the prior art, the beneficial technical effects of the present invention are as follows: 1: The present invention uses relatively cheap inert perfluoropolyether oil as raw material, and catalytically cracks it with a magnesium-based catalyst to obtain a relatively expensive active perfluoropolyether single-end carboxylic acid product, and the active perfluoropolyether single-end carboxylic acid accounts for as high as >99.0%, and the functionality can be as high as >0.99, and the product has extremely high added value.
[0027] 2: The magnesium-based catalyst described in the present invention has low cost, simple preparation method, relatively mild cracking reaction conditions, can stably control the cracking reaction process, and has high selectivity for active perfluoropolyether single-end carboxylic acid products.
[0028] 3: The process flow for preparing active perfluoropolyether single-end carboxylic acid of the present invention is simple, the reaction conditions are mild, the operation is easy, the target product has a wide range of applications, and has high market economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of Catalyst I prepared in Preparation Example 1 of the present invention.
[0030] Figure 2 This is the SEM image of Catalyst II prepared in Preparation Example 2 of the present invention.
[0031] Figure 3 This is the SEM image of Catalyst VIII prepared in Preparation Example 2 of the present invention.
[0032] Figure 4 This is a SEM image of Catalyst VIII prepared in Preparation Example 8 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is illustrated below by way of example, and the scope of protection requested by the present invention includes but is not limited to the following embodiments.
[0034] Source of experimental raw materials: Perfluoropolyether oil: weight average molecular weight is about 21870 g / mol, Solvay Group, kinematic viscosity is 550 CST (20°C). Note: The technical solution of this application is applicable to all perfluoropolyether oils. The perfluoropolyether oil used in the examples is only used to verify the effect of the technical solution and cannot limit the treatment of all perfluoropolyether oils.
[0035] Preparation Example 1 Weigh 16.8 g of magnesium nitrate hexahydrate and add it to 50 ml of deionized water to dissolve, stir it evenly under a magnetic stirrer at 500 rpm, and this is referred to as liquid A; weigh 9.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, stir it evenly under a magnetic stirrer at 500 rpm, and this is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the reaction was carried out at 30°C for 6 hours. After the reaction, the reaction liquid was centrifuged at a speed of 5000 rpm. The lower layer of the reaction liquid was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. After that, the catalyst precursor was ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 700°C at a rate of 5°C / min in a muffle furnace and calcined for 2 hours to obtain catalyst I.
[0036] Preparation Example 2 Weigh 16.8 g of magnesium nitrate hexahydrate and 4.2 g of zinc nitrate hexahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add them to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst II (the molar ratio of magnesium to zinc was approximately 1:0.22).
[0037] Preparation Example 3 Weigh 16.8 g of magnesium nitrate hexahydrate and 3.0 g of zinc nitrate hexahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add them to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst III (the molar ratio of magnesium to zinc was approximately 1:0.15).
[0038] Preparation Example 4 Weigh 16.8 g of magnesium nitrate hexahydrate and 2.0 g of zinc nitrate hexahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add them to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The mixture was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst IV (the molar ratio of magnesium to zinc was approximately 1:0.10).
[0039] Preparation Example 5 Weigh 16.8 g of magnesium nitrate hexahydrate and 5.8 g of zinc nitrate hexahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add them to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain a catalyst V (the molar ratio of magnesium to zinc was approximately 1:0.30).
[0040] Preparation Example 6 Weigh 16.8 g of magnesium nitrate hexahydrate and 7.8 g of zinc nitrate hexahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add them to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst VI (the molar ratio of magnesium to zinc was approximately 1:0.40).
[0041] Preparation Example 7 Weigh 16.8 g of magnesium nitrate hexahydrate and 1.2 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add them to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst VII (the molar ratio of magnesium to manganese is approximately 1:0.07).
[0042] Preparation Example 8 Weigh 16.8 g of magnesium nitrate hexahydrate, 4.2 g of zinc nitrate hexahydrate, and 1.2 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst VIII (the molar ratio of magnesium, zinc and manganese elements is approximately 1:0.22:0.07).
[0043] Preparation Example 9 Weigh 16.8 g of magnesium nitrate hexahydrate, 4.2 g of zinc nitrate hexahydrate, and 1.7 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain a catalyst IX (the molar ratio of magnesium, zinc and manganese elements is approximately 1:0.22:0.1).
[0044] Preparation Example 10 Weigh 16.8 g of magnesium nitrate hexahydrate, 4.2 g of zinc nitrate hexahydrate, and 2.5 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A under stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain a catalyst X (the molar ratio of magnesium, zinc and manganese elements was approximately 1:0.22:0.15).
[0045] Preparation Example 11 Weigh 16.8 g of magnesium nitrate hexahydrate, 4.2 g of zinc nitrate hexahydrate, and 0.9 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst XI (the molar ratio of magnesium, zinc and manganese elements was approximately 1:0.22:0.05).
[0046] Preparation Example 12 Weigh 16.8 g of magnesium nitrate hexahydrate, 4.2 g of zinc nitrate hexahydrate, and 0.5 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst XII (the molar ratio of magnesium, zinc and manganese elements is approximately 1:0.22:0.03).
[0047] Comparative Example 1 Weigh 14.0 g aluminum nitrate, 4.2 g zinc nitrate hexahydrate, and 1.2 g manganese nitrate tetrahydrate, add them to 60 ml deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g sodium carbonate and add it to 40 ml deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst XIII (the molar ratio of aluminum, zinc and manganese elements is approximately 1:0.22:0.07).
[0048] Comparative Example 2 Weigh 12.3 g of copper nitrate, 4.2 g of zinc nitrate hexahydrate, and 1.2 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The catalyst precursor was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain catalyst XIV (the molar ratio of copper, zinc and manganese elements is approximately 1:0.22:0.07).
[0049] Comparative Example 3 Weigh 19.1 g of cobalt nitrate hexahydrate, 4.2 g of zinc nitrate hexahydrate, and 1.2 g of manganese nitrate tetrahydrate, add them to 60 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid A; weigh 10.6 g of sodium carbonate and add it to 40 ml of deionized water to dissolve, and stir them evenly under a magnetic stirrer at 500 rpm, which is referred to as liquid B; Liquid B was added dropwise to liquid A while stirring, and the mixture was reacted at 35°C for 6 hours. After the reaction, the reaction solution was centrifuged at a speed of 5000 rpm. The lower layer of the reaction solution was washed with water until the pH value was 7, and then dried in an oven at 80°C for 24 hours. The mixture was then ground through a 200-mesh sieve to obtain a catalyst precursor. Finally, the catalyst precursor was heated to 650°C in a muffle furnace at a rate of 5°C / min and calcined for 3 hours to obtain a catalyst XV (the molar ratio of cobalt, zinc and manganese elements was approximately 1:0.22:0.07).
[0050] Application Example 1 Weigh 0.5g of catalyst I, 60g of perfluoropolyether oil (weight average molecular weight of about 21870g / mol) and 60mL of trifluorotrichloroethane into a 200ml thick-walled three-necked flask, and stir at 800rpm for 5min for pre-dispersion treatment, then react at 215℃ and 600rpm for 18min, stop heating after the time is up, and wait for the reaction mixture to cool naturally to room temperature; Take 10g of the cooled reaction mixture and filter it, transfer the filtrate to a 100ml conical flask, then add 10mL of SV70 solvent and 6ml of hydrochloric acid solution (mass fraction of 5%), and stir at 500rpm for 5min for acidification. After acidification, transfer the acidified solution to a 100ml separatory funnel, add 10ml of acetonitrile, shake the mixture and let it stand for stratification, collect the lower layer solution, and extract it repeatedly three times. Transfer the lower layer solution to a 100ml eggplant-shaped bottle, remove the solvent by vacuum rotary evaporation at 60°C to obtain a crude product. The crude product is separated by wet chromatography column, and after separation, the solvent is removed by vacuum rotary evaporation at 60°C to obtain about 4.42g of active perfluoropolyether single-end carboxylic acid product. GPC analysis of the product showed that its weight average molecular weight was about 6414 g / mol, the proportion of active perfluoropolyether single-end carboxylic acid was about 89.3%, the functionality was about 1.01, and the yield was about 44.2% (based on the total mass of the reaction mixture after cooling).
[0051] Catalysts II to XV were used to replace the catalyst I in Application Example 1 in sequence, and the test process of Application Example 1 was repeated. The test result data of each catalyst was recorded as shown in the following table:
[0052] As can be seen from the above table, the method of the present invention can catalyze and crack perfluoropolyether oil with high selectivity under the action of a homemade magnesium-based catalyst to obtain active perfluoropolyether single-end carboxylic acid (Z-type) with suitable weight average molecular weight with high selectivity, and the synthesis conditions are mild, the process is short and easy to control, and the yield is high. It provides abundant raw materials for the modification of functional functional groups of active perfluoropolyether single-end carboxylic acid products and the fluorine-modified materials used in various fields, which can be widely used in the fields of coatings and surface treatment materials, etc., and has significant market prospects and huge social and economic value.
Claims
1. A method for preparing perfluoropolyether carboxylic acid using perfluoropolyether oil, characterized in that: The method specifically comprises the following steps: firstly, mixing perfluoropolyether oil and a fluorine-containing solvent in the presence of a magnesium-based catalyst to obtain a reaction mixture; then, separating the reaction mixture, and sequentially acidifying and purifying the separated filtrate to obtain the target perfluoropolyether carboxylic acid.
2. The method according to claim 1, characterized in that: The weight average molecular weight of the perfluoropolyether oil is not less than 10,000, preferably not less than 20,000; and / or The fluorine-containing solvent includes one or more of m-ditrifluorotoluene, trichlorotrifluoroethane, dichloropentafluoropropane, and hexafluoroisopropanol, preferably trichlorotrifluoroethane.
3. The method according to claim 1 or 2, characterized in that: The volume ratio of the perfluoropolyether oil to the fluorinated solvent is 1:0.5-5, preferably 1:0.8-3; and / or The amount of the magnesium-based catalyst used is 0.1-2% by mass of the perfluoropolyether oil, preferably 0.5-1.5%.
4. The method according to any one of claims 1 to 3, characterized in that: The magnesium-based catalyst is prepared by the following method: firstly dissolving a water-soluble magnesium salt in water to obtain a magnesium-based salt solution, then adding a soluble carbonate to the magnesium-based salt solution for precipitation reaction, and finally heat-treating the solid product obtained by the reaction to obtain the magnesium-based catalyst; Preferably, the magnesium-based catalyst is prepared by the following method: firstly dissolving a water-soluble magnesium salt and a water-soluble zinc salt in water to obtain a magnesium-based salt solution, then adding a soluble carbonate to the magnesium-based salt solution for precipitation reaction, and finally heat-treating the solid product obtained by the reaction to obtain the magnesium-based catalyst; Further preferably, the magnesium-based catalyst is prepared by the following method: firstly dissolving a water-soluble magnesium salt, a water-soluble zinc salt, and a water-soluble manganese salt in water to obtain a magnesium-based salt solution, then adding a soluble carbonate to the magnesium-based salt solution for a precipitation reaction, and finally heat-treating the solid product obtained by the reaction to obtain a magnesium-based catalyst.
5. The method according to claim 4, characterized in that: The water-soluble magnesium salt includes one or more of magnesium nitrate, magnesium sulfate, and magnesium chloride; the water-soluble zinc salt includes one or more of zinc nitrate, zinc sulfate, and zinc chloride; the water-soluble manganese salt includes one or more of manganese nitrate, manganese sulfate, and manganese chloride.
6. The method according to claim 5, characterized in that: In the magnesium-based catalyst, the molar ratio of magnesium element, zinc element and manganese element is 1:0-0.35:0-0.12, preferably 1:0.15-0.3:0.05-0.
1.
7. The method according to any one of claims 4 to 6, characterized in that: The soluble carbonate includes one or more of sodium carbonate, potassium carbonate, lithium carbonate and ammonium carbonate; Preferably, the carbonate is added in an amount such that the content of carbonate ions in the reaction system is not less than 1.2 to 1.5 times the content of magnesium ions.
8. The method according to any one of claims 4 to 7, characterized in that: The precipitation reaction temperature is 20-60°C, preferably 30-50°C; the precipitation reaction time is 1-12h, preferably 2-10h; and / or The heat treatment is calcining at a temperature of 400-900° C. for 1-8 hours, preferably calcining at a temperature of 500-800° C. for 2-6 hours.
9. The method according to any one of claims 1 to 3, characterized in that: The mixing reaction is a stirring reaction, the stirring reaction temperature is 120-280° C., preferably 150-250° C.; the stirring reaction time is 10-90 min, preferably 15-60 min.
10. The method according to any one of claims 1 to 3, characterized in that: The acidification is specifically as follows: adding a solvent (such as perfluoropolyether solvent SV70) and a hydrochloric acid solution to the filtrate and then stirring; wherein: the amount of the solvent added is 0.05 to 0.3 times the volume of the filtrate; the hydrochloric acid solution is a dilute hydrochloric acid solution with a mass concentration of 3 to 15%, and the amount of the hydrochloric acid solution added is 0.2 to 1 times the volume of the filtrate; the stirring speed is 300 to 1000 rpm, and the stirring time is 1 to 30 minutes; and / or The purification specifically includes: adding a solvent (such as acetonitrile) to the acidified liquid obtained after the acidification treatment for extraction, collecting the lower layer solution after standing, and performing a reduced pressure evaporation treatment to remove the solvent.